Staphylococcus saccharolyticus infection: case series with a PRISMA-compliant systemic review - Wang, Ping (Medicine (Baltimore), 2020)
BACKGROUND: Staphylococcus saccharolyticus is a rare cause of human infectious disease. The clinical characteristics and treatment of patients with S saccharolyticus infections remain largely unknown. OBJECTIVES: We present the first reported case of empyema due to S saccharolyticus. In addition, a systematic review and pooled analysis of all S saccharolyticus cases were done to summarize the clinical and microbiological characteristics and treatment of this rare pathogen. METHODS: A case of empyema caused by S saccharolyticus diagnosed in study hospital was reported. This case and those identified from PubMed, EMBASE, and Web of Science were analyzed. RESULTS: In total, 8 patients were reviewed. The averages of the white blood cell count, sedimentation rate, and C-reactive protein were 16.8 × 10(9)/L, 72 mm/h, and 176 mg/L, respectively. The average time-to-positivity of the anaerobic cultures was 5 days. The S saccharolyticus was resistant to metronidazole, but susceptible to fluoroquinolones, clindamycin, and vancomycin in all the cases with drug sensitivity tests available for these antibiotics. Two of 7 patients showed resistance to all β-lactams. Both of those patients finally died. CONCLUSIONS: S saccharolyticus should be added to the list of anaerobic microorganisms that are able to cause empyema. A prolonged anaerobic culture is critical to improve the yield of this possibly underestimated pathogen. The time to positive culture of S saccharolyticus may not help to distinguish true-positive growth from contaminated growth. Acute or subacute courses and systemic evidence of infection may contribute to judge the clinical significance of positive cultures and avoid unnecessary antibiotic treatment. β-Lactam agents plus fluoroquinolones or vancomycin/teicoplanin or clindamycin may be appropriate to achieve full coverage of the β-lactam resistant bacteria.